Digital Technology And The Real Estate Industry (Economic and Bussiness Faculty, Dr Soetomo University, 2019)
This paper briefly summarises the extent of the technological impact on the real estate industry, in particular, digital technology. As real estate industry is naturally characterized by several disadvantages in comparison to other industry, understanding the impact of digital technology is crucial to the industry on whether this technology will distrust the industry or complement the business process. The emergence of PropTech start-ups has made the industry players to re-evaluate its organisational strategy to align the business process to a possible threat to the present business model. Prior studies suggest that PropTech comes in there waves in which each wave is characterized by the respective period advancement in digital technology. Several studies also indicate that digital technology may not entirely disrupt the industry but do have a significant potential to act as a complement to the industry in improving its productivity and efficiency.